Время войны: [16+] / Станислав Сергеев - Сергеев Станислав (Боевая фантастика, 2013)
Экземпляры: Аб (20150414) / Инвентарный номер: 102530 / Цена: 160.00 / Авт.знак: С 32 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6